2002
DOI: 10.1097/00002030-200210180-00002
|View full text |Cite
|
Sign up to set email alerts
|

Hypersusceptibility to non-nucleoside reverse transcriptase inhibitors in HIV-1

Abstract: NNRTI hypersusceptibility is common among patient HIV-1 isolates, especially in NRTI-resistant viruses. Genotypic correlates of hypersusceptibility are complex and not easily defined by a simple analysis of NRTI-associated resistance mutations. NNRTI hypersusceptibility may provide an explanation for the superior virologic response to NNRTI-containing salvage regimens observed in NRTI-experienced patients in several clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
3
3

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 8 publications
2
42
3
3
Order By: Relevance
“…The same model could also be used to explain the hypersusceptibility to two of the protease inhibitors where the selected mutations did not provide cross-resistance. However, we cannot exclude the possibility that some RTV resistance-associated mutations simply enhance binding of some inhibitors, as has been suggested for some reverse transcriptase inhibitors (69).…”
Section: Discussionmentioning
confidence: 89%
“…The same model could also be used to explain the hypersusceptibility to two of the protease inhibitors where the selected mutations did not provide cross-resistance. However, we cannot exclude the possibility that some RTV resistance-associated mutations simply enhance binding of some inhibitors, as has been suggested for some reverse transcriptase inhibitors (69).…”
Section: Discussionmentioning
confidence: 89%
“…The routine use of highly reproducible phenotypic assays (24) revealed that many clinical HIV-1 isolates exhibited significant hypersusceptibility (defined as a change in the 50% inhibitory concentration versus the reference of Յ0.4-fold) to the non-nucleoside reverse transcriptase inhibitor class (12,31,34). This phenomenon is associated with previous nucleoside analogue treatment and with an increase in the efficacy of salvage antiretroviral regimens including non-nucleoside reverse transcriptase inhibitors (12,31,32,34).…”
mentioning
confidence: 99%
“…This phenomenon is associated with previous nucleoside analogue treatment and with an increase in the efficacy of salvage antiretroviral regimens including non-nucleoside reverse transcriptase inhibitors (12,31,32,34). In chronically infected antiretroviral-experienced patients, amprenavir hypersusceptibility is associated with the N88S mutation in protease, which is not seen in drug-naïve patients (26,35).…”
mentioning
confidence: 99%
“…Phenotypic hypersusceptibility of HIV-1, defined as having a greater than 2.5 fold increase in susceptibility to a drug compared with a wild-type reference strain using the phenotypic resistance assay by Monogram Biosciences (formerly ViroLogic), occurs with protease inhibitors and non-nucleoside reverse transcriptase inhibitors (NNRTIs) [17][18][19][20] . HIV-1 variants with phenotypic NNRTI hypersusceptibility are more likely to be resistant to nucleoside analogs 17,[20][21][22] . In patients, the presence of HIV-1 with NNRTIhypersusceptibility is associated with improved responses to an NNRTI-containing regimen compared to patients with variants that are not hypersusceptible 8,20,21,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Early reports identified an association between phenotypic NNRTI-hypersusceptibility and thymidine analog mutations (i.e., those at codons 41, 67, 70, 210, 215 and 219 of reverse transcriptase) 17,22 . One study reported a correlation between phenotypic efavirenz hypersusceptibility and a number of different reverse transcriptase mutations in univariate analyses, including T215Y/F, D67N, H208Y, K103R, and V179D 24 .…”
Section: Introductionmentioning
confidence: 99%